SISTEM INFORMASI SELEKSI PENERIMA PROGRAM INDONESIA PINTAR DENGAN MENGGUNAKAN METODE MAUT - Elyana Elyana; Ai Illah Warnilah (STIKOM CKI, 2018)
ABSTRACT With the development of the internet that could make people easier to access various information that is happening, as well as information for government assistance, one of them is assistance for students that can reduced the cost of education with the existence of government assistance in the form of Smart Indonesian Program through Smart Indonesian Card. Yayasan Islam Elementary School of Tasikmalaya is an institution engaged in education. In this school, Smart Indonesian Program reception was still manual starting from recording, recapping and making reports were still done one by one which make the lack of data accuracy. For that the author try to make the final project about Information System of Smart Indonesian Program Receiver Selection Using Maut (Multy Attribute Utility Theory) Method in Yayasan Islam Elementary School because it is not computerized yet, the system carried out in this school is still manual. In this System Design, author used Maut Method for decision support systems so that the school can select underprivillaged students easily from determined criterias, This Information System Design is the best solution for solve problems that exist in school with Maut Method could find students who are untitled and not untitled for Smart Indonesian Program assistance. In this selection, the highest value was 2,16 and the lowest value was 0,90.